Gallstone Ileus Managed with One-Stage Laparotomy : A Rare Case Report - Nindya Wiharjanto, Dorothy Eugene; Adnyana, Ida Bagus Budhi Surya; Heryadi, Afrizal Tri (Smart Medical Journal, 2025)
Introduction: Gallstone ileus is defined as a mechanical intestinal obstruction due to impaction of one are more gallstones within the gastrointestinal tract. Gallstone ileus has shown a constant incidence of 30-35 cases/1000000 admissions over a 45-year period. Most of the symptoms and signs of gallstone ileus are nonspecific. Case Presentation: A 61-year-old man presented with abdominal pain and vomiting 3 days prior to hospital admission. The abdominal pain was felt on all of the regions of the abdomen and did not subside with rest. The patient has a history of having gallstones on November 2021. On 3 views abdominal x-ray, it showed high-grade ileus. Exploratory laparotomy with ileal enterotomy were performed incidentally to evacuate the gallstones and continued with cholecystectomy. The patient’s condition had improved after receiving surgery. We also provided post-operative pain management and maintained the fluid, electrolyte, and metabolic balances for the patient. Discussion: Gallstone ileus is a rare complication of cholelithiasis. Its intermittency of symptoms could also interfere the diagnosis. Therefore, it is associated with relatively high rates of morbidity and mortality. The main therapeutic goal of gallstone ileus is a relief of intestinal obstruction by evacuating the gallstones.Conclusion: Because of nonspecific signs and symptoms, the diagnosis of gallstone ileus is often delayed. It is mostly an incidental finding during abdominal procedures. Therefore, it should be considered in patients presenting with bowel obstruction and known gallstone disease.